Rare Presentation of Emphysematous Cystitis with Culture-Proven Urosepsis in a Geriatric Female: A Case Report - Maharsi, Chiendo Yurinda; Ali Husein (Open Access Indonesian Journal of Medical Reviews, 2025)
Emphysematous cystitis (EC) is a rare and potentially life-threatening infection of the bladder wall characterized by the presence of gas. It predominantly affects elderly females with diabetes mellitus. While the clinical presentation can vary, it commonly involves symptoms of urinary tract infection. This case report describes an unusual presentation of EC in a geriatric female complicated by culture-proven urosepsis. A 66-year-old female with a history of type 2 diabetes mellitus presented to the emergency department with fever, dyspnea, and tachypnea. She reported suprapubic pain, dysuria, and foul-smelling, murky urine for two days. Initial laboratory findings revealed leukocytosis, hyperglycemia, and elevated procalcitonin levels, indicating sepsis. Computed tomography (CT) of the abdomen and pelvis revealed air foci within the bladder wall, consistent with EC. Blood and urine cultures grew Escherichia coli resistant to multiple antibiotics but susceptible to amikacin and gentamicin. The patient was treated with intravenous amikacin and showed significant clinical improvement, with subsequent negative urine cultures. In conclusion, our study highlights a rare presentation of emphysematous cystitis complicated by culture-proven urosepsis in a geriatric female with multidrug-resistant Escherichia coli. Prompt diagnosis using CT imaging and appropriate antibiotic therapy based on culture sensitivities led to a successful outcome. This case underscores the importance of considering EC in elderly diabetic patients presenting with sepsis and urinary symptoms, even with atypical features.